Glycosyl hydrolases from Bifidobacterium adolescentis DSM 2008 : - Broek, van den L A M (Wageningen Universiteit, 2005)
To obtain more information about their carbohydrate modifying enzymes, a genomic library of B. adolescentis DSM20083 was constructed and screened for glycosyl hydrolases.